Kajian Form of Place pada Kawasan PKOR Way Halim Bandar Lampung Sebagai Destinasi Ruang Terbuka Publik Kota - Ikhsan Da’i, R; Hizbullah Sesunan, M.M (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2024)
Cultural and Sports Center Area (PKOR) is a public open space that is one of the landmarks of Way Halim Area, Bandar Lampung City. PKOR area is used for various big events and trading activities as well as a place to exercise, which makes this place always visited by people from various regions. Public open space facilities that are pretty complete increase the desire of the community to keep returning. The existing sports and cultural activities fill the PKOR area, making it a public space. This research focuses on examining one of the factors that form a sense of place, namely form (place), which is a factor that can turn space into place. This research aims to examine the form (place) in the PKOR area. This research uses a descriptive qualitative method with primary data collection by collecting respondent data and directly observing activities in the PKOR area. The study results show that the area's physical form greatly influences various aspects of public open space in developing a destination, so the arrangement of the number and type of physical attributes significantly affects place-making.